Non-invasive assessment of tissue sodium content in patients with primary adrenal insufficiency - Chifu, Irina; Weng, Andreas Max; Burger-Stritt, Stephanie; Bley, Thorsten Alexander; Christa, Martin; Köstler, Herbert; Hahner, Stefanie (European journal of endocrinology, 2022)
Objective Replacement therapy in primary adrenal insufficiency (PAI) with corticosteroids modulates sodium homeostasis. Serum sodium is, however, prone to osmotic shifts induced by several additional factors besides corticosteroids and does not always reliably reflect treatment quality. Non-osmotic tissue storage can be visualized by sodium MRI (23Na-MRI) and might better reflect corticosteroid activity. Design Longitudinal study of 8 patients with newly diagnosed PAI and cross-sectional study in 22 patients with chronic PAI is reported here. Comparison was made with matched healthy controls. Methods Using a 23Na-MRI protocol on a 3T scanner, relative sodium signal intensities (rSSI) to signal intensities of the reference vial with 100 mmol/L of sodium were determined in the muscle and skin of the lower calf. Results In newly diagnosed patients, tissue rSSI (median, range) were reduced and significantly increased after treatment initiation reaching levels similar to healthy controls (muscle: from 0.15 (0.08, 0.18) to 0.18 (0.14, 0.27), P = 0.02; skin: from 0.12 (0.09, 0.18) to 0.18 (0.14, 0.28), P < 0.01). Muscle rSSI was significantly higher in patients with chronic PAI compared to controls (0.19 (0.14, 0.27) vs 0.16 (0.12, 0.20), P < 0.01). In chronic PAI, skin rSSI significantly correlated with plasma renin concentration. Conclusion 23Na-MRI provides an additional insight into sodium homeostasis, and thus the quality of replacement therapy in PAI, as tissue sodium significantly changes once therapy is initiated. The increased tissue sodium in patients with chronic PAI might be an indication of over-replacement.